Karakteristik kebahasaan perempuan dalam film pendek Capciptop: sebuah kajian atomisme logis - Wibawani, Sri; Rohman, Saifur (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to describe the linguistic characteristics of Javanese women in Capciptop short film from the perspective of logical atomism. This research includes qualitative research with a sociolinguistic approach. The data of this research is the speech of female characters with the data source comes from the short film Capciptop found on the youtube channel Ravacana Films. The data collection was conducted using the technique of simak catatat by referring to Lakoff's linguistic theory and Russel's logical atomism. The results showed that there are three dominant characteristics of women's language in Capciptop short film, namely (1) intensifier (women often use intensifying words in their speech); (2) avoidance of strong swear words (women tend to avoid harsh swear words and prefer to express annoyance with a more subtle version), and (3) tag question (women often give emphasis at the end of a sentence to emphasize, ask for approval, or confirm something). From the view of logical atomism, these three linguistic characteristics reflect the social reality that develops in society about the character of womanhood, including (1) women like to exaggerate speech; (2) women as marginalized people who are guided to speak politely; and (3) women like to gossip.